Complexities of Care in the Political Aspirations of Finnish Girls - Suni, Anna; Åberg, Erica; Mietola, Reetta (Routledge, 2026)
This article explores aspirations concerning future and political participation of Finnish adolescent girls. We analyse data produced in 2018 by 856 girls aged 13–20 in response to a questionnaire. We ask (1) what futures do the girls see as possible and desirable for themselves and (2) what kind of political agency is constructed in the girls’ accounts? While our interest in political participation has steered our analysis, the thematic analysis led us to focus on the changing and sustaining possibilities available for the girls and especially the process by which these girls are becoming (political) agents within the plurality of discourses defining contemporary femininities. Drawing on feminist literature on girls’ agency, girl power and care our analysis highlights the complexities of care entangled in the political agency, actions and (gendered) societal expectations visible in the girls’ responses. We develop the concept of triple burden to describe the contradictory terrain where the emancipated strong and active girls are imagining their future.